The Use of Stories in Tourism Public Relations - Awaloedin, Dipa Teruna; Pradini, Gagih; Azhar, Muhammad Faris; Andini, Davi Ayu (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
The tourism industry has experienced significant evolution, driven by technological advancements, internet accessibility, and evolving consumer preferences. Consequently, Public Relations (PR) has become vital for shaping and enhancing the positive image of tourism destinations globally. As competition intensifies and communication technologies evolve, tourism organisations must innovate communication strategies to remain competitive. Storytelling has emerged as a powerful tool in tourism PR, offering unique abilities to captivate audiences, evoke emotions, and deepen experiences. Compelling storytelling can influence destination perceptions, engage emotions, strengthen stakeholder relationships, and navigate the digital landscape. This paper explores the impact, strategies, and implications of storytelling in tourism PR, providing insights for practitioners and decision-makers in the tourism industry.